Sink-Convergence Cascading Model for Wireless Sensor Networks with Different Load-Redistribution Schemes. (19th June 2019) - Fu, Xiuwen; Yao, Haiqing; Yang, Yongsheng
Abstract : Existing cascading models are unable to depict the sink-convergence characteristic of WSNs (wireless sensor networks). In this work, we build a more realistic cascading model for WSNs, in which two load-redistribution schemes (i.e., idle redistribution and even redistribution) are introduced. In addition, failed nodes are allowed to recover after a certain time delay rather than being deleted from the network permanently. Simulation results show that the network invulnerability is positively correlated to the tolerance coefficient and negatively correlated to the exponential coefficient. Under the idle-redistribution scheme, the network can have stronger invulnerability against cascading failures. The extension of the recovery time will exacerbate the fluctuation of the cascading process.